Fermented Perilla frutescens Ameliorates Depression-like Behavior in Sleep-Deprivation-Induced Stress Model - Jee, Hye Jin; Ryu, Dajung; Kim, Suyeon; Yeon, Sung Hum; Son, Rak Ho; Hwang, Seung Hwan; Jung, Yi Sook (International Journal of Molecular Sciences, 2023)
Excessive stress plays a critical role in the pathogenesis of mood disorders such as depression. Fermented natural products have recently attracted attention because of their health benefits. We evaluated the antidepressant-like efficacy of fermented Perilla frutescens (FPF), and its underlying mechanisms, in sleep deprivation (SD)-induced stress mice. SD-stressed mice revealed a remarkable increase in the immobility time in both forced swimming test and tail suspension test; this increase was ameliorated by treatment with FPF at doses of 100 and 150 mg/kg. FPF treatment also reduced the level of stress hormones such as corticosterone and adrenocorticotropic hormone. Additionally, FPF increased the levels of serotonin and dopamine which were significantly decreased in the brain tissues of SD-stressed mice. The increased expression of proinflammatory cytokines, such as TNF-α and IL1β, and the decreased expression of brain-derived neurotrophic factor (BDNF) in the stressed mice were significantly reversed by FPF treatment. Furthermore, FPF also increased phosphorylation of tropomyosin receptor kinase B (TrkB), extracellular regulated protein kinase (ERK), and cAMP response element binding protein (CREB). Among the six components isolated from FPF, protocatechuic acid and luteolin-7-O-glucuronide exhibited significant antidepressant-like effects, suggesting that they are major active components. These findings suggest that FPF has therapeutic potential for SD-induced stress, by correcting dysfunction of hypothalamic-pituitary-adrenal axis and modulating the BDNF/TrkB/ERK/CREB signaling pathway.
Keywords: Animals; Antidepressive Agents; Brain-Derived Neurotrophic Factor; Depression; Disease Models, Animal; Hippocampus; Hypothalamo-Hypophyseal System; Mice; Perilla frutescens; Pituitary-Adrenal System; Sleep Deprivation; Stress, Psychological; BDNF; corticosterone; depression; fermented Perilla frutescens; sleep deprivation; stress